Assessment and Optimization of Ecological Networks in Trans-Provincial Metropolitan Areas—A Case Study of the Xuzhou Metropolitan Area - Yijia Zhao; Peiyuan Zhang; Hao Xu; Wei Liu (Land)
In the urbanization development trend, constructing inter-provincial metropolitan areas has gradually become an important pathway for China to implement its new urbanization strategy. Economic development in metropolitan areas inevitably leads to ecological degradation and fragmentation, threatening biodiversity. A reasonable assessment and optimization of the ecological network structure of inter-provincial metropolitan areas can effectively improve the stability of regional ecosystems and contribute to the sustainable development of urban and rural environments. In this study, we optimized the identification of ecological sources at the metropolitan area scale by constructing the ‘MIE’ model combined with the threshold analysis method, identified the core ecological sources in the Xuzhou Metropolitan Area, a typical cross-provincial metropolitan area in China, and then extracted the ecological corridors by using the Linkage Mapper tool based on this method. The spatiotemporal patterns and components of the ecological network of the Xuzhou metropolitan area from 1990 to 2020 were assessed, and an optimization analysis was performed based on the current ecological network. The results show that urban expansion has caused a decentralized layout of the ecological space in the study area across the provincial metropolitan area, with an uneven distribution of ecological sources and the development of ecological corridors in an east-dense and west-sparse pattern in 30 years. Increased interference by human activities has decreased the landscape dominance of the regional ecological resources and overall fragmentation of the habitats. The number of ecological corridors decreased, the average length of ecological corridors increased, the difficulty of biological flow increased, the connectivity of the ecological network structure decreased, and accessibility between source areas decreased. The α, β, and γ indices of the regional ecological network increased by 0.16, 0.46, and 0.1, respectively, after restoring important ecological sources and corridors. This study provides a framework for ecological network assessment and optimization in cross-provincial metropolitan areas, which is of great significance for studying metropolitan areas at similar stages of development.